2020
DOI: 10.1177/1071100720950741
|View full text |Cite
|
Sign up to set email alerts
|

Titrating the Amount of Bony Correction in Progressive Collapsing Foot Deformity

Abstract: Recommendation: There is evidence indicating that the amount of bony correction performed in the setting of progressive collapsing foot deformity reconstructive surgery can be titrated within a recommended range for a variety of procedures. The typical range when performing a medial displacement calcaneal osteotomy should be 7 to 15 mm of medialization of the tuberosity. The typical range when performing an Evans lateral column lengthening should be 5 to 10 mm of a laterally based wedge in the anterior calcane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Compensatory forefoot supination/varus has been demonstrated in the setting of a planovalgus deformity and often is partially corrected with an opening wedge medial cuneiform osteotomy (Cotton osteotomy). 1,4,7,10,16,18 Furthermore, forefoot driven hindfoot varus in a cavovarus foot may be treated partially with a dorsiflexion M1 osteotomy. 21 Both these approaches correct sagittal plane deformities without appreciation of a potential rotatory abnormality of the first metatarsal.…”
Section: Discussionmentioning
confidence: 99%
“…Compensatory forefoot supination/varus has been demonstrated in the setting of a planovalgus deformity and often is partially corrected with an opening wedge medial cuneiform osteotomy (Cotton osteotomy). 1,4,7,10,16,18 Furthermore, forefoot driven hindfoot varus in a cavovarus foot may be treated partially with a dorsiflexion M1 osteotomy. 21 Both these approaches correct sagittal plane deformities without appreciation of a potential rotatory abnormality of the first metatarsal.…”
Section: Discussionmentioning
confidence: 99%
“…The angle measurement and arch height of the models were similar to those of the PCFD population. 3,9,12,13,25,31,32,39,41,47 The comparison results between the rectangle and triangular grafts suggested that the correcting ability of rectangle grafts was stronger than that of triangular grafts. However, the contact characteristics of the calcaneocuboid joint and talonavicular joint were abnormal, whereas the strain of the spring ligament even increased.…”
Section: Discussionmentioning
confidence: 99%
“…The goal is to correct the valgus hindfoot into neutral or slightly valgus by distracting the short arm osteotomy about 6 to 8 mm in length with a wedge strut allograft inserted into the gap. 15 The posterior fragment was carefully controlled to ensure good contact with the subtalar part of the osteotomy. Percutaneous Kirschner wires (23 cases) or a 2.7-mm locking plate (3 early cases) was used for fixation.…”
Section: Operative Proceduresmentioning
confidence: 99%